Western Transmedia Projects in China: Growing Phenomenon with Cross-Cultural Challenges? - Ilya A. Bykov; Xiaorui Gao (Галактика медиа: журнал медиа исследований)
In recent years, many Western transmedia projects have entered into the Chinese market, with their own cultural influences. In this situation, we should pay attention to how Chinese transmedia projects are developing, what are the collisions between Chinese and Western cultures, and what are the opportunities and challenges brought by transmedia projects. The purpose of this research is to understand the popularity of Western transmedia projects in China, to examine the reasons for their popularity, and to recognize the opportunities and challenges in this situation. The study uses mixed methodology: secondary data analysis, online survey, and in-depth personal interviews. It has been found that Western transmedia projects are popular in China due to the cultural, technical, and promotional reasons which have been discussed in details. One of the reasons for Western transmedia projects been not popular deals with the problem of cultural distance and alienation.